PHÂN LẬP VÀ ĐỊNH DANH MỘT SỐ CHỦNG NẤM SỢI TRÊN KHÍ TÀI QUANG TẠI BẮC GIANG - VIỆT NAM - Ngô, Cao Cường; Đỗ, Tất Thịnh; Chu, Thanh Bình; Phí, Quyết Tiến; Nguyễn, Văn Đức (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
ISOLATION AND IDENTIFICATION OF SOME FUNGAL SPECIES ON MILITARY OPTICAL EQUIPMENT IN BAC GIANG - VIETNAM The 13 fungi were isolated from five optical equipments collected in Bac Giang province, Viet Nam. These fungi were classified as Aspergillus and Penicillium. Based on classification by morphology and sequence of ITS1 - 5,8S - ITS2 regions, three fungi were identified including 13.1 - Aspergillus flavus; 19.1 - Aspergillus aculeatus and 17.2 - Aspergillus niger.